Drug delivery systems for prolonged duration local anesthesia. Issue 1 (January 2017) - Santamaria, Claudia M.; Woodruff, Alan; Yang, Rong; Kohane, Daniel S.
Abstract : Numerous drug delivery systems have been applied to the problem of providing prolonged duration local anesthesia (PDLA). Here we review the rationale for PDLA, the desirable features for and important attributes of such systems, and specific examples that have been developed.